Analysis of Factors for Implementing TPM: A Study in Welded Tube Manufacturers - Oliveira, Rodolfo Alves de [UNESP]; Muniz, Jorge [UNESP]; Marins, Fernando A. S. [UNESP]; Grabot, B.; Vallespir, B.; Gomes, S.; Bouras, A.; Kiritsis, D. (Springer, 2014)
This study aims to identify and assess critical factors influencing on the implementation of continuous improvement projects, specifically the TPM. This research is a quali-quanti study and collects data with managers who lead TPM implementation in the shop floor. In this perspective, the present work can contribute to production managers with an assessment of the critical factors that will assist in decision-making processes for implementing improvement projects and troubleshooting methods, more specifically based on the TPM and Autonomous Maintenance.
Keywords: Total Productive Maintenance; Critical factors; Continuous improvement projects; Welded tube industries